Selection of Technological Parameters of Selective Laser Melting of Mechanocomposite Ti–Nb Powder; Inorganic Materials: Applied Research; Vol. 10, iss. 1 - Kovalevskaya Zh. G. Zhanna Gennadievna; Fedorov V. V. Vasilii Viktorovich; Krinitsyn M. G. Maksim Germanovich; Klochkov N. S. Nikolay Sergeevich; Khimich M. A. Margarita Andreevna; Sharkeev Yu. P. Yury Petrovich (2019, 2019)
Title screen